2020
DOI: 10.36351/pjo.v36i4.1109
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effect of Intravitreal Bevacizumab Injection on Intraocular Pressure

Abstract: Purpose:  To determine the immediate effect of intravitreal Bevacizumab on intraocular pressure (IOP) in eyes with retinal vascular disorders. Study Design:  Interventional case series. Place and Duration of Study:  Ophthalmology Department, Fauji Foundation Hospital, Rawalpindi, from January 2019to July 2019. Methods:  One hundred and thirty one patients were included in this study using non probability consecutive sampling. IOP was measured before intravitreal injection (baseline) and at 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…One of the complications is raised intraocular pressure, but its duration of elevation is important. 11,12 Our study found that the dose of intravitreal injection of Bevacizumab has a shorter-term elevation of IOP. There is a rise in IOP at 5min after the procedure, which returns to <21mmhg at 30 min to 1 hour.…”
Section: Discussionmentioning
confidence: 65%
“…One of the complications is raised intraocular pressure, but its duration of elevation is important. 11,12 Our study found that the dose of intravitreal injection of Bevacizumab has a shorter-term elevation of IOP. There is a rise in IOP at 5min after the procedure, which returns to <21mmhg at 30 min to 1 hour.…”
Section: Discussionmentioning
confidence: 65%
“…8,9 Zafar A et al, showed that IOP was increased during initial 5 minutes and normalized at the end of one-hour post-injection. 10 Qureshi et al, studied the effect of ocular decompression at injection site just before intravitreal injection. They divided 100 eyes into 2 groups, decompression followed by IVB and IVB without decompression.…”
Section: Discussionmentioning
confidence: 99%
“…8 Another recent study on the Pakistani population by Zafar et al, evaluated the effects of intravitreal Bevacizumab injections on IOP and had similar results to our research. 12 They concluded that significant IOP elevation occurred during the immediate post-op period. 12 However, the difference with our study was that the IOP returned to near normal at 30 minutes post-injection in most of their study population, while our patients had sustained rise in IOP even after 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…12 They concluded that significant IOP elevation occurred during the immediate post-op period. 12 However, the difference with our study was that the IOP returned to near normal at 30 minutes post-injection in most of their study population, while our patients had sustained rise in IOP even after 30 min. Our results were in coherence with the results of the de Vries et al, metaanalysis that showed that IOP remained significantly high on the day of injection, with multiple time interval readings and showed a downward trend from the next day onwards.…”
Section: Discussionmentioning
confidence: 99%